The pandemic continues to strain nursing homes. What happens if a lot of them close? - Padilla, Mariel (The 19th, 2021)
Thousands of nursing homes say they are struggling to keep their doors open during the pandemic. The 19th reached out to experts to discuss what mass closures would mean for the aging and their loved ones.
Keywords: Nancy Kusmaul